2020
DOI: 10.1002/jgh3.12347
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of osteoporotic status in outpatients who underwent gastrectomy for gastric cancer

Abstract: Background and Aim: Disorders in bone metabolism have long been recognized as typical sequelae of gastrectomy; however, the pathogenesis has not been fully elucidated, resulting in a variation of reported incidence. This study aimed to evaluate current bone health by measuring bone mineral density (BMD) in patients treated by gastrectomy for gastric cancer, with a focus on incidence and risk factors of osteoporosis. Methods: The study enrolled 81 patients who underwent gastrectomy for gastric cancer at Kochi M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…With the increasing number of long-term survivors after gastrectomy, there has been increasing interest in the clinical management of post-gastrectomy syndromes and their possible complications. Among these complications, several reports indicated that patients with gastric cancer, and particularly gastric cancer survivors who underwent gastrectomy, have an increased risk of osteoporosis and fragility fractures [ 153 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ]. This is in keeping with previous observations in patients with gastrectomy for peptic ulcer disease [ 169 ].…”
Section: Gastric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing number of long-term survivors after gastrectomy, there has been increasing interest in the clinical management of post-gastrectomy syndromes and their possible complications. Among these complications, several reports indicated that patients with gastric cancer, and particularly gastric cancer survivors who underwent gastrectomy, have an increased risk of osteoporosis and fragility fractures [ 153 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ]. This is in keeping with previous observations in patients with gastrectomy for peptic ulcer disease [ 169 ].…”
Section: Gastric Disordersmentioning
confidence: 99%
“…Likewise, the presence of complications, such as diabetes or dyslipidemia, as well as chemotherapy, have been associated with a higher risk of fracture after gastrectomy [ 163 ]. Anemia and a reduction in hemoglobin levels have been also linked to a higher risk of bone fragility in gastric cancer patients [ 167 , 168 ]. Although the underlying mechanism remains to be fully understood, it is likely that increased oxidative stress and extracellular acidification under hypoxic conditions might negatively affect bone remodeling, as also observed in the general population [ 180 , 181 ].…”
Section: Gastric Disordersmentioning
confidence: 99%
“…Several studies on GC and osteoporosis or osteoporotic fractures have indicated that female sex, old age, and low body mass index are risk factors for developing osteoporosis. However, most studies were conducted at a single center, with a relatively small number of patients [12,[16][17][18][19]. Some studies included only men [20] or did not use matched controls [12,16,18,21].…”
Section: Introductionmentioning
confidence: 99%